iSeedTM phosphorus coating of oat grains to improve seedling establishment and early growth - Kontturi, Markku; Peltonen-Sainio, Pirjo; Lähdetie, Pasi; Peltonen, Jari (MTT, 2004)
The phosphorus (P) is transformed in soil into unavailable forms for plant due to the high content of active iron (Fe) and aluminium (Al) in acid soils, and due to the high content of calcium (Ca) in alkaline soil. The utilization rate of phosphorus in granular fertilizers is about 10-15% in the first year, but only 1-2% per year there after. iSeed - Intelligent seed is an early growth promoter for the crop. In the iSeed P solution seeds are coated with highsoluble phosphate and biodegradable fixing agent. Coating the seed with soluble P fertilizer improves the utilization rate of phosphorus, when the key nutrient is just in place for the early root and canopy growth. In 2003 three cultivars of oats (Salo, Fiia, Belinda) were grown on two soil types low in phosphorus (P-values 4 to 8 mg/L soil). Experimental design was split-plot: cultivars in main plots and treatments (untreated control or iSeed ) in sub plots. At planting all plots received 400 kg/ha NPK fertilizer (20-3-8) as deep placement between seed rows. Planting density was 500 viable seeds/m2. After emergence the density of treatments was monitored two times by counting the plants (one meter in five rows per plot). Early growth of the oats was measured three times by sampling biomass (50 randomly chosen plants per plot) in weekly intervals. Grain yields of oat cultivars were high ranging from 470 to 595 g m2 in exp 1 and 550 to 680 g m2 in exp 2. Cultivar differences were evident, but coating oat grains with iSeed did not increase grain yield. The plant stand structure differed, however, greatly between iSeed treated and control plants. iSeed treatment resulted in higher biomass of oat plants. How this associates with differences in seedling establishment will be further studied in 2004.
Keywords: Ka; kaura; siemen; pinnoite; iSeed; fosfori; kasvu; lajike; kasvusto; oats; phosphorus; iSeed; growth; biomass; yield